Reconciling biogeochemical redox proxies: tracking variable bottom water oxygenation during OAE-2 using vanadium isotopes - Li, Siqi; Friedrich, Oliver; Nielsen, Sune G.; Wu, Fei; Owens, Jeremy D. (Earth and planetary science letters, 2023)
Oceanic Anoxic Event-2 (OAE-2, ∼94 Ma ago) is marked by a significant perturbation to the carbon and nutrient cycles. Despite the general idea of widespread expansion of the oceanic anoxia during OAE-2, various localities likely experienced heterogeneous redox fluctuations throughout the roughly 500-thousand-year-long event. In certain localities, redox-sensitive elements imply persistent anoxic-to-euxinic conditions, notwithstanding paleontological data that indicate short-term hypoxic-to-anoxic oscillations in bottom waters. Such discrepancies likely result from sampling resolution, local proxy sensitivity, and/or time-integration of signals, particularly for severe hypoxic conditions. We applied vanadium (V) isotopes to three well-studied OAE-2 localities in the proto-North Atlantic Basin. Under the relatively stable anoxic-to-euxinic conditions throughout OAE-2 at Well S75 and Site 367, the sedimentary δ51V values present consistent variations analogous to modern anoxic-to-euxinic environments. However, at Site 1258, the sedimentary δ51V values present greater perturbations toward more negative values that are indicative of short-term oxygenation in bottom waters. These negative perturbations of δ51V values covary with the abundances of the low-oxygen-tolerant benthic foraminifers. Together, these data refine the heterogeneous redox fluctuations in individual localities, revealing occasional short-term weak oxygenation under the generally anoxic conditions throughout OAE-2. This study documents the unique utility of V isotopes to track bottom water redox fluctuations, particularly short-term variations from anoxic to mildly oxic conditions that are hard to track with other methods.